Dysregulated microRNAs in blood correlate with central nervous system neuropathology of prion disease - Sonia Pérez-Lázaro; Inmaculada Martín-Burriel; Luca Cozzuto; Julia Ponomarenko; Juan J. Badiola; Rosa Bolea; Janne M. Toivonen (Veterinary Research)
Abstract The role of microRNAs (miRNAs) in neurodegenerative diseases has gained significant attention because of their involvement in gene regulation and potential as biomarkers. In prion diseases, including scrapie, miRNAs may modulate pathogenesis and disease progression. This study investigated circulating miRNA profiles in the blood of sheep naturally affected by scrapie at preclinical and clinical stages using small RNA sequencing and RT-qPCR validation. While only one novel miRNA was dysregulated in preclinical blood samples, 66 previously annotated miRNAs were significantly dysregulated in clinical sheep compared with healthy sheep. These miRNAs are associated with pathways commonly altered in neurodegenerative diseases, such as autophagy, ubiquitin-mediated proteolysis, and endoplasmic reticulum protein processing. Notably, miR-1271-5p, let-7f-5p, miR-186-5p, and miR-425-5p were consistently upregulated in the central nervous system of clinical animals, replicating the results observed in blood, with an increasing trend already in the preclinical stage and a strong correlation with neuropathological prion features. Additionally, predicted target genes such as UBQLN2, PGK1, KRAS, and CLTC were inversely expressed relative to these miRNAs, supporting their regulatory roles. These findings highlight the relevance of circulating miRNAs in prion neuropathology and support further research into the specific functional roles of these miRNAs and their predictive capacity for disease progression.